FACTORS AFFECTING THE AIR-BONE GAP IN PATIENTS WITH CHRONIC OTITIS MEDIA INDICATED FOR SURGERY AT THAI BINH MEDICAL UNIVERSITY HOSPITAL - Khiếu, Hữu Thanh; Đặng, Tuấn Phong; Trần, Mạnh Cường; Vũ, Ngọc Thoan; Lê, Thị Ánh Tuyết; Nguyễn, Thị Hải Yến; Panhchakrith, Thong; Vũ, Trung Kiên; Ngô, Thanh Bình (Tạp chí Tai Mũi Họng Việt Nam, 2024)
Objective: To analyze some factors affecting the air-bone gap (ABG) in patients with chronic otitis media at Thai Binh Medical University Hospital. Method: A case series study was conducted on 94 patients with chronic otitis media undergoing tympanoplasty at Thai Binh Medical University Hospital from 2017-2023. Results: Large perforations had the highest incidence (39.4%). Conductive hearing loss accounted for the majority of cases (75.5%), with most cases being mild (54.3%). The site and size of the perforation, as well as ossicular chain lesions, had a statistically significant effect on ABG. The anterior perforation group and the small perforation group exhibited the least hearing loss, both with a median ABG of 17.5 dB. In the presence of ossicular chain lesions, the ABG was even greater, with a value of 32.5 dB. Only ossicular chain lesions had a statistically significant effect on the ABG on multivariate linear regression Conclusion: The condition of ossicles chain lesions significantly affect the ABG in chronic otitis media.